A systematic review on the physical, mental, and occupational effects of exercise on pregnant women - Nathalia Rodrigues-Denize; By Tara Rava Zolnikov; Frances Furio (Elsevier, 2024)
Complications in pregnancy have been proven to be less frequent with exercise. The American College of Obstetrics and Gynecology suggests pregnant women should exercise an average of 20 to 30 min a day; however, only 13% of pregnant women exercise throughout their pregnancy. This amount could be improved if women are aware that exercise: 1. Can help avoid pregnancy complications or death and 2. Comes in various forms with different health outcomes associated with it. For this reason, this systematic literature review was conducted to review different types of exercise for pregnant women. Peer-reviewed articles were selected to discuss the benefits of the most researched exercises for pregnant women, which included yoga, resistance training, aquatic exercises, dance, and aerobic exercise such as running, walking, and cycling. Data from the review revealed that different types of exercises led to various benefits at different stages of pregnancy. Aquatic activities and yoga helped pregnant women toward the end of their pregnancies, whereas resistance training, dance, and aerobic exercises provided the most benefits during the first trimester. Other studies found that any form of exercise for 30 min a day or every other day for 60 min provided extensive beneficial results. Ultimately, this information could be used to create individualized exercise plans for pregnant women to adhere to throughout their pregnancy.